An Impact of Stress on Women Employees with Reference to Selected Bpo’s Visakhaptnam (International Journal of Scientific Research and Management (IJSRM), 2017)
Stress can be defined as a pressure (or) tension exerted on a material object (or) a state of mental (or) emotional strain (or) tension resulting from adverse (or) demanding circumstances. Stress can’t be avoided, but one can learn how to manage it. District like Visakhapatnam in the recent years has shown mammoth developments in the field of outsourcing sector. In the case of Information Technology Enabled Services (ITES), Business Process Outsourcing (BPO’s) in particular, majority are women employees who are working for it. This study highlights the critical need to investigate the countless pressure for women workers in the BPO industry. The present Study is based on a sample of 72 women employees from various BPO’s in Visakhapatnam, majority of which were experienced more than 2 years. Here the discussion is what changes are required to manage stress among working women and what is being done to get the best practices for BPO industry. For that we framed set of questioners for analysis and to lock the predominant factor that causes stress and to provide best solutions to overcome from it